COVID-19 vaccine hesitancy: assessing the prevalence, predictors, and effectiveness of a community pharmacy based counseling intervention - Joshua Kiptoo; John Isiiko; Tadele Mekuriya Yadesa; Tumugumye Rhodah; Paul E. Alele; Edgar Mugema Mulogo (BMC, 2024)
Abstract Background Coronavirus disease (COVID-19) vaccine hesitancy is a global challenge. In low- and middle-income countries (LMICs), the problem has persisted despite vaccine availability and decreasing infections. In Uganda, there is still limited information on the extent and predictors of vaccine hesitancy. This study sought to assess the prevalence and predictors of COVID-19 vaccine hesitancy, and the effectiveness of an intervention that involved community pharmacy counseling in combating COVID-19 vaccine hesitancy. Methods A total of 394 participants were enrolled in a 4-week prospective cohort interventional study. The study was conducted across eight community pharmacies in Mbarara City, between 9:00 AM and 5:00 PM daily. The study personnel ascertained the vaccination status of all clients seeking community pharmacy services. All unvaccinated clients were consecutively assessed for eligibility, and eligible clients were systematically enrolled after receiving the community pharmacy services for which they requested. The study intervention involved structured participant counseling (within the pharmacy premise), follow-up short message service (weekly), and telephone calls (bi-weekly). Only participants who did not accept to receive the COVID-19 vaccine despite counseling were followed up for four weeks, or until they accepted to receive a COVID-19 vaccine. The effectiveness of the community pharmacy counseling intervention was determined as an increase in COVID-19 vaccine acceptance, and desirable attitudinal change towards COVID-19 disease, vaccination exercise, and vaccines. Descriptive analysis was used to summarize data, and multivariate analysis was used to determine the predictors of COVID-19 vaccine hesitancy. A p-value < 0.05 was considered statistically significant. Results Out of 394 participants, 221 (56%) were hesitant to receive a COVID-19 vaccine. Participants expressed several reasons (mean 2±1) for COVID-19 vaccine hesitancy, mostly concerning vaccine safety (N=160, 47.3%). The overall COVID-19 vaccine acceptance rate increased by 25.4 percent points (43.9 - 69.3 percent points) after the study intervention. Age, religion, level of education, distance from the nearest public health facility, having a friend/family diagnosed with COVID-19, and personal suspicion of contracting COVID-19 were significant predictors of COVID-19 vaccine hesitancy. Conclusion COVID-19 vaccine hesitancy is a big challenge in Uganda. A mix of sociodemographic and COVID-19 vaccine perceptions are the key predictors of COVID-19 vaccine hesitancy. Although COVID-19 vaccines were not available at the time of the study, this study found that structured counseling interventions can improve COVID-19 vaccine acceptance rates. Larger prospective studies should evaluate the effectiveness of similar interventions in community pharmacies and other healthcare settings.